P65 Effect of the COVID-19 pandemic on chlamydia testing and diagnosis within Scotland's largest sexual health service. (16th June 2022) - Holt, Rebecca; Kennedy, Richard
Abstract : Introduction: This study evaluates the impact of the re-introduction of self-selection for sexual health screening following the COVID-19 pandemic on chlamydia testing and diagnoses within Scotland's largest sexual health service. There was an additional focus on identifying groups that may have been excluded by the current testing strategies and groups where a higher incidence of chlamydia has been noted. Methods: We identified all chlamydia tests and diagnoses across our service between August to October 2021, compared to March 2019 to February 2020. Data describing demographics were also extracted. To simplify comparisons between cohorts, the results within each group were converted into a cohort proportions. Descriptive analysis was used to compare cohorts. We offer a limited service for at-home self-testing, outsourced to an external company, which was not included in our testing figures; positive samples will have been captured in this analysis due to how they are reported locally. Results: A 9% decrease was seen in testing after COVID although diagnoses remained at similar level to that pre-COVID. Testing rates were lower and positive rates were greater in areas where there currently aren't any testing centres. Testing rates were also lower in females and under 25-year-olds. Discussion: It is difficult to draw final conclusions about increased chlamydia prevalence in demographic groups due to how outsourced tests and positive cases are recorded on our EPR, but what has been clearly demonstrated is the need for increased access to testing in localities where local testing clinics have been closed during the pandemic.